Effect of acute maximal exercise on vasodilatory function and arterial stiffness in African-American and white adults. Issue 6 (June 2019) - Schroeder, Elizabeth C.; Ranadive, Sushant M.; Yan, Huimin; Lane-Cordova, Abbi D.; Kappus, Rebecca M.; Cook, Marc D.; Fernhall, Bo
Abstract : Introduction: African-Americans are at increased risk of cardiovascular disease compared with their white counterparts, potentially due to greater arterial stiffness and reduced vasodilatory capacity. Racial differences also exist in arterial stiffness and blood pressure (BP) following maximal aerobic exercise; African-Americans do not exhibit central post exercise BP reductions. Whether impaired vasodilatory function contributes to the lack of BP response is unknown. Purpose: To evaluate vasodilatory function, arterial stiffness, and hemodynamics following a maximal aerobic exercise test in young, healthy African-American and white adults. Methods: Twenty-seven African-American and 35 white adults completed measures at baseline, 15 and 30 min after a maximal exercise test. Measures included vasodilatory capacity of forearm resistance arteries, central pulse wave velocity (PWV), and carotid artery stiffness (β). Results: Forearm reactive hyperemia was greater in white but increased similarly following exercise in both groups ( P < 0.05). Carotid β-stiffness increased at 15 and 30 min ( P = 0.03) in both groups, but PWV controlled for mean arterial pressure decreased after maximal exercise ( P = 0.03). White exhibited reductions in systolic and mean pressure, whereas no changes were seen for African-Americans (interaction effects: P < 0.05). Conclusion: African-American and white adults had similar decreases in PWV, increases in β-stiffness, and increases in vasodilatory function following maximal exercise. African-American adults, however, did not display reductions in BP and had overall lower vasodilatory function in comparison with white adults. Our results suggest African-Americans exhibit similar vasodilatory function changes following aerobic exercise as their white counterparts, and therefore vasodilatory function likely does not explain the lack of BP response in African-Americans. Abstract : Supplemental Digital Content is available in the text